Verbascum duzgunbabadagensis (Scrophulariaceae), a new species from eastern Anatolia, Turkey - Karavelioğulları, Faik Ahmet; Yüce, Ebru; Başer, Birol (Phytotaxa, 2014)
Verbascum duzgunbabadagensis (Scrophulariaceae) is described and illustrated as a new species endemic to eastern Anatolia, Turkey. In this study, diagnostic morphological characters of this and closely related species (V. luciliae and V. rupicola) are discussed. Pollen and seed morphology of the new species and of similar taxa are documented. The seeds of this group are brown in color and oblong in V. luciliae and V. rupicola, whereas they are dark brown in color and ovate in shape in V. duzgunbabadagensis. Furthermore, distribution maps for the three taxa are provided.